Economic evaluations of public health implementation-interventions: a systematic review and guideline for practice. (April 2019) - Reeves, P.; Edmunds, K.; Searles, A.; Wiggers, J.
Abstract: Objectives: Implementation interventions applied in public health are about using proven strategies to influence the uptake of evidence-based prevention and health promotion initiatives. The decision to invest in implementation has an opportunity cost, which can be overlooked. The purpose of this study was to assess the extent to which economic evaluations have been applied to implementation interventions in public health. Study design: We conducted a systematic review of empirical studies examining the costs and consequences, cost-effectiveness or cost-benefit of strategies directed towards enhancing the implementation of public health interventions and policies in developed countries. Methods: The following databases were searched for English language publications reporting both effect measures and costs, from 1990 to current: MEDLINE, Embase, PsycINFO, CINAHL, EconLit, EPPI-Centre database of health promotion research, Cost-Effectiveness Analysis Registry, NHS Economic Evaluation Database, Informit and Scopus. Results: The search strategy returned 3229 records after duplicate removal, from which we included 14 economic evaluations. All the included evaluations were conducted and published after 2000. Twelve of the 14 evaluations were based on controlled trials and two reported hypothetical modelled scenarios. The methodologic rigour and compliance with reporting guidelines for economic evaluations was highly varied and not related to the publication date. Conclusions: Our findings offer the first insight into the application and methodologic rigour of economic evaluations of implementation strategies supporting public health policies and interventions. To usefully inform public health policy and investment decisions, there needs to be greater application of economic evaluation to understand the cost-effectiveness of alternative implementation efforts. This review highlights the great paucity and mixed quality of the evidence on this topic and offers guidance by way of a checklist to improve the quality and reporting of future evaluations. Highlights: Public health policy could benefit from increased application of economic evaluation. Implementation in public health has an opportunity cost, which is often overlooked. Practical guidance is required to promote economic evaluation of public health implementation investment.